Aspects of Leadership Ethics, Law, and Spirituality - Connelley, Carroll; Tripodi, Paolo (Marine Corps University Press (MCUP), 2012)
Aspects of Leadership is a new book edited by Lieutenant Colonel Carroll Connelley and Dr. Paolo Tripodi, the Ethics Branch head, and comprised of essays by a group of 20 leadership and ethics scholars and practitioners. The Lejeune Leadership Institute Ethics Branch, Marine Corps University, provides current and relevant scholarly research and instruction on ethics and moral leadership and the law of war. This collection of essays provides timely and insightful views on current leadership behavior and ethical concerns that men and women of the armed forces face in the demanding, complex, and prolonged decade of armed conflict.